Food Consumption and Nutrient Density of Adults Male Aged 19-49 Years Old in Indonesia - Teguh Jati Prasetyo; Izzati Nur Khoiriani; Katri Andini Surijati (Journal of Global Nutrition, 2021)
The objectives of this study was to analyze food consumption and nutrient density of adults male aged 19-49 years old in Indonesia. This study was carried out through analyzing a consumption data set of Total Diet Study (SDT) of Indonesian Ministry of Health which were collected using 24-hour food recall method. The final subjects included for this study were 26268 male. The nutrients adequacy were assessed based on Institute of Medicine calculation. The nutrients analyzed include energy, protein, calcium, iron, zinc, vitamin A and vitamin C. The average food consumption of Indonesian adult male population is mostly from the grains food group of 305.0 g. The food group that was consumed the least by the adult population was oily seeds as much as 18.1 g. The adequacy of energy, protein, calcium, iron, zinc, vitamin A and vitamin C were 81.4%, 108.3%, 105.5%, 159.4%, 64.8%, 107.7% and 54.6%, respectively. The nutrient density of protein, Ca, Zn, vitamin A and vitamin C were still under the recommendation. It means that food consumption quality of Indonesian adults need to be improved. Considering the inadequate intake of some micronutrients in Indonesian adults male, it is necessary to increase the consumption of animal food, legumes, fruits and vegetables as sources of micronutrients.